PENDAPAT MASYARAKAT TERHADAP DAMPAK LINGKUNGAN PETERNAKAN AYAM PETELUR (Studi Kasus Di Dusun Semanding Desa Kawedusan Kecamatan Ponggok Kabupaten Blitar) - Diki Wijayanto; Agustina Widyasworo; Risma Novela Esti (AVES: Jurnal Ilmu Peternakan, 2021)
The research was conducted in Semanding Hamlet Kawedusan Village Ponggok District, Blitar Regency. The purpose of this study was to determine public opinion on the environment of laying chicken farm. The research uses survey research type. The are 433 households with a total population of 2.167 people and there are 12 laying chicken farm with a livestock population of 428.000 heads. The sample 18with a total of 82 respondents. The data in this study were obtained using observation, interviews, and documentation. The analysis technique descriptive. The research results obtained can be described as : viewed from the aspect of air pollution and water sources are not good but the community understands that permits are allowed by community as well as district/city government, employment is very beneficial and the reciprocal relationship between farmers and the community is very important good, the results obtained that the existence of laying chicken farm does not interfere with the community. However, even though the residents are not disturbed, they still maintain the waste managemen